PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN: CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING - Isnaini, Nurizza Arsyi; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to examine the influence of the characteristic of the company which is proxy byprofitability and leverage to the firm value with corporate social responsibility as the intervening variable. Theresearch samples are 33 mining companies which are listed in Indonesia Stock Exchange and have publishedtheir annual report in 2013-2015 periods and have carried out Corporate Social Responsibility (CSR). The CSRhas been measured by using GRI G4. The ample collection has been carried out by using purposive samplingmethod. The hypothesis has been tested by using multiple linear regressions analysis and the SPSS 23rd version.The result of research shows that the characteristic of the company which is proxy by profitability and leveragedoes not have any influence to the firm value. Meanwhile, the characteristic of the company which is proxy byprofitability has positive influence to the CSR and leverage does not have any influence to the CSR. Meanwhile,CSR has positive influence to the firm value. The result of the research shows that CSR is not the interveningvariable under the influence of the characteristic of the company to the firm value.Keywords: Profitability, leverage, corporate social responsibility, firm value.